2020
DOI: 10.1039/d0sc00135j
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free carbon monoxide-releasing micelles undergo tandem photochemical reactions for cutaneous wound healing

Abstract: Metal-free carbon monoxide-releasing polymers (CORPs) are synthesized via a direct polymerization approach, exhibiting not only improved stability but also accelerated wound healing performance as compared to CORM-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 62 publications
1
52
0
Order By: Relevance
“…Such assemblies have precedent as Cheng et al have reported micelles where the photo-activated carbon monoxide-releasing 3-hydroxyflavone moiety is located on the interior with PEG groups extending into the aqueous medium. [22] Having obtained evidence of micelle formation, we selected the more soluble and faster releasing oCOm-54 as a suitable candidate for pharmacological studies ( Figure 5). Both oCOm-54 and oCOm-21 caused a concentration-dependent vasorelaxation response in isolated rat aortas preconstricted with phenylephrine (100 nM).…”
Section: Resultsmentioning
confidence: 99%
“…Such assemblies have precedent as Cheng et al have reported micelles where the photo-activated carbon monoxide-releasing 3-hydroxyflavone moiety is located on the interior with PEG groups extending into the aqueous medium. [22] Having obtained evidence of micelle formation, we selected the more soluble and faster releasing oCOm-54 as a suitable candidate for pharmacological studies ( Figure 5). Both oCOm-54 and oCOm-21 caused a concentration-dependent vasorelaxation response in isolated rat aortas preconstricted with phenylephrine (100 nM).…”
Section: Resultsmentioning
confidence: 99%
“…4-(Bromomethyl)-3-nitrobenzaldehyde (compound 1) and 3-hydroxy-2-(4-(hydroxymethyl)phenyl)-4H-benzo[g]chromen-4-one (compound 3) were synthesized according to the reported procedures. [32,37] Characterization: 1 H and 13 C NMR spectra were recorded on a 400 MHz Bruker nuclear magnetic resonance (NMR) spectrometer. Deuterated chloroform (CDCl 3 ) and dimethyl sulfone (DMSO-d 6 ) were used as the solvents.…”
Section: Methodsmentioning
confidence: 99%
“…[24,31] To address this problem, we recently developed a CO-releasing polymer that can selectively release CO under visible light irradiation by the introduction of 3-hydroxyflavone (3-HF) derivatives. [32] Notably, the photooxygenation of 3-HF moieties with the release of CO was characterized by remarkable fluorescence changes, allowing for direct monitoring of the CO release in a self-reporting manner. However, it should be mentioned that the installation of the CO-releasing 3-HF moieties in the pendant chains rendered the resulting block copolymer non-degradable, which was an obstacle for the Carbon monoxide (CO) has emerged as a potential therapeutic agent for the treatment of many diseases.…”
Section: Doi: 101002/marc202000323mentioning
confidence: 99%
See 1 more Smart Citation
“…Although CO could readily bind to many transition metals, conventional metal carbonyl-based CORMs suffer from several limitations such as insufficient stability in a biological condition, spontaneous release, and limited action time. To this end, much effort has been devoted to the development of metal-free CO donors and some successful examples have been reported, including 3-hydroxyflavone (3-HF) derivatives [ 62 ], xanthene-9-carboxylic acid [ 63 ], boron dipyrromethene (BODIPY) [ 64 ], and aromatic α-diketone derivatives [ 65 ]. Despite tremendous achievements, the development of CO-releasing MOFs is rather sparse.…”
Section: Mofs For the Delivery Of Carbon Monoxidementioning
confidence: 99%